Impact of Public Transport Infrastructure Investment on Economic Growth in Nepal - Acharya, Khubi Ram; Ojha, Krishna Prasad; Upreti, Surendra (NCC Journal, 2024)
This paper assesses the relationship between public transport infrastructure investment and economic growth in Nepal using time series data. The study uses Vector Error Correction Model (VECM) to study the short and long-run relationship between public transport infrastructure investment and economic growth in Nepal during the period from 1974-2019. The study finds that in the short run, there is an initial negative impact of public transport infrastructure investment on economic growth, which attenuates over time and eventually transitions to a positive effect. The study concludes that while challenges persist, strategic investments in public transport infrastructure remain a cornerstone for Nepal's journey towards sustained economic growth, prosperity, and inclusive growth.